Evaluation of Undergraduate Students’ Skills for Online Learning in Nigeria - Mary Kehinde Salawu; Ganiyat Temitope Azeez; Boniswa T Madikizela (INVOTEC, 2022)
The study assessed the relevance of the skills required of undergraduate students towards online learning as well as evaluated the skills possessed by them for online learning. The study employed a descriptive survey research design. The population of the study comprised undergraduate students from the faculties of administration, science, and social science at Obafemi Awolowo University, Nigeria. A simple random sampling method was adopted to select 375 respondents from the faculties.  Data were collected using a structured questionnaire that was emailed to respondents and analysed using frequency distribution tables and the chi-square method.The study revealed that personal and technical skills are extremely important for online learning, with average values exceeding the 2.5 standard, indicating that they are required. Also, the students possessed an appreciable number of personal skills that are conducive to online learning. However, students were not well-grounded in technical skills such as good control of database management software, Microsoft Excel, and so on. The study recommends that the university system should implement a hybrid lecture system in which students participate in a blended learning system. Additionally, more technical skill orientations, lectures, seminars, or workshops should be provided to help students improve technical abilities.